CERITA RAKYAT JAKA BANDUNG: ANALISIS STRUKTURAL LEVI-STRAUSS - Pipit Mugi Handayani Handayani (Universitas PGRI Semarang, 2013)
Through folktales, people can express their mindset they had during the period of the tale. Folktales usually have myths that accompany the story. In this research, a folktale that will be discussed is a tale called ?óÔé¼?ôJaka Bandung?óÔé¼?Ø, a story that comes from Prambanan area, Central Java and has been published. This folktale is one of the versions of the oral tales spread and grew in central java that used Levi-Strauss?óÔé¼Ôäó structuralism analysis. The steps in the research is done by finding the mytheme and arrange the mytheme sintagmatically and paradigmatically. ?é?á Keywords: folktales, myth, mytheme, pattern